2017
DOI: 10.1002/jor.23502
|View full text |Cite
|
Sign up to set email alerts
|

ACL injury reduces satellite cell abundance and promotes fibrogenic cell expansion within skeletal muscle

Abstract: Anterior cruciate ligament (ACL) injuries are associated with significant loss of strength in knee extensor muscles that persists despite physical therapy. The underlying mechanisms responsible for this protracted muscle weakness are poorly understood; however, we recently showed significant myofiber atrophy and altered muscle phenotype following ACL injury. We sought to further explore perturbations in skeletal muscle morphology and progenitor cell activity following an ACL injury. Muscle biopsies were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
68
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 51 publications
5
68
0
Order By: Relevance
“…However, recent studies have pointed to clear evidence of maladaptive muscle responses, with ACL-R patients demonstrating increased circulating levels of the atrophy-inducing signaling molecules myostatin and transforming growth factor-b up to 5 weeks after surgical repair, 3 and decreased quadriceps muscle stem cell density and muscle fiber CSA. 16,17 This is further supported by animal studies that reported reduced in vitro whole muscle force production after ACL tear, with increased expression of atrophy-associated genes such as the E3 ubiquitin ligases atrogin-1, MuRF-1, and MUSA-1 that can target proteins for enzymatic breakdown. 18,19 In the current study, the lack of appreciable changes in fiber CSA along with substantial changes in F o , suggest that there is a marked reduction in the density of myofibrils, which are the force generating organelles in muscle fibers.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…However, recent studies have pointed to clear evidence of maladaptive muscle responses, with ACL-R patients demonstrating increased circulating levels of the atrophy-inducing signaling molecules myostatin and transforming growth factor-b up to 5 weeks after surgical repair, 3 and decreased quadriceps muscle stem cell density and muscle fiber CSA. 16,17 This is further supported by animal studies that reported reduced in vitro whole muscle force production after ACL tear, with increased expression of atrophy-associated genes such as the E3 ubiquitin ligases atrogin-1, MuRF-1, and MUSA-1 that can target proteins for enzymatic breakdown. 18,19 In the current study, the lack of appreciable changes in fiber CSA along with substantial changes in F o , suggest that there is a marked reduction in the density of myofibrils, which are the force generating organelles in muscle fibers.…”
Section: Discussionmentioning
confidence: 75%
“…Much of the literature on neuromuscular changes in ACL‐R patients has not considered intrinsic changes to the muscle fibers themselves. However, recent studies have pointed to clear evidence of maladaptive muscle responses, with ACL‐R patients demonstrating increased circulating levels of the atrophy‐inducing signaling molecules myostatin and transforming growth factor‐β up to 5 weeks after surgical repair, and decreased quadriceps muscle stem cell density and muscle fiber CSA …”
Section: Discussionmentioning
confidence: 99%
“…Skeletal muscle often displays chronic degenerative changes following injury, including atrophy and weakness of muscle fibers, and fibrotic changes to the extracellular matrix (1)(2)(3)(4). Some muscles also display a pathological accumulation of lipid in response to chronic injury or disease, which is referred to as myosteatosis or fatty degeneration (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Skeletal muscle often displays chronic degenerative changes following injury, including atrophy and weakness of muscle fibers and fibrotic changes to the extracellular matrix (ECM) (1)(2)(3)(4). Some muscles also display a pathologic accumulation of lipid in response to chronic injury or disease, which is referred to as myosteatosis or fatty degeneration (5,6).…”
mentioning
confidence: 99%